Development of a Rhythmic Gymnastics Learning Model to Improve the Motor Skills of Students with Mild Intellectual Disabilities - Agung Nugroho; Andri Arif Kustiawan; Nazwa Amalia (Universitas Pendidikan Ganesha, 2026)
Students with mild intellectual disabilities often experience limitations in motor development, particularly in coordination, balance, flexibility, and movement control, which affect their participation in physical education learning. Existing learning practices tend to rely on conventional instructional approaches and have not optimally accommodated the characteristics and learning needs of students with intellectual disabilities. This study aimed to develop, analyze, and evaluate the effectiveness of a rhythmic gymnastics learning model in improving the motor skills of students with mild intellectual disabilities. The study employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research involved 30 students with mild intellectual disabilities, while data were collected through observation, expert validation questionnaires, motor skill assessment sheets, and documentation. The developed instruments were validated by experts before implementation, and the collected quantitative and qualitative data were analyzed descriptively to evaluate the feasibility and effectiveness of the learning model. The findings indicate that the developed rhythmic gymnastics learning model is feasible, practical, and effective in enhancing students' motor skills, particularly in movement coordination, balance, flexibility, and muscle strength. These findings suggest that the developed learning model can serve as an innovative instructional alternative for adaptive physical education while supporting the improvement of motor competence among students with mild intellectual disabilities.